Proteomic analysis of the aqueous humour in eyes with pseudoexfoliation syndrome. Issue 8 (6th March 2019) - Botling Taube, Amelie; Konzer, Anne; Alm, Albert; Bergquist, Jonas
Abstract : Background/aims: Pseudoexfoliation syndrome (PEX) is characterised by the production and accumulation of extracellular fibrillar material in the anterior segment of the eye. The pathogenesis of PEX is multifactorial with genetic factors and ageing as contributing factors. Previously, an increased concentration of beta-crystalline B2 (CRYBB2) was observed in the aqueous humour (AH) in eyes with PEX in a pooled material. Here, the protein content was examined on individual basis. Methods: During cataract surgery, AH was sampled from patients with and without PEX, 10 eyes in each group. The proteins were digested and labelled with isotopomeric dimethyl labels, separated with high-pressure liquid chromatography and analysed in an Orbitrap mass analyzer. Results: The concentration of complement factor 3, kininogen-1, antithrombin III and vitamin D-binding protein was increased in all eyes with PEX. Retinol-binding protein 3, glutathione peroxidase, calsyntenin-1 and carboxypeptidase E were decreased in eyes with PEX. Beta-crystalline B1 and CRYBB2 and gamma-crystalline D were up to eightfold upregulated in 4 of 10 in eyes with PEX. Conclusion : The results indicate that oxidative stress and inflammation are contributing factors in the formation of PEX. Knowledge about the proteome in PEX is relevant for understanding this condition.